The effects of early nutritional contents in premature infants on the development and severity of retinopathy: A retrospective case-control study - Mustafa Şenol Akın; Şule Yiğit (Trends in Pediatrics)
Objectives: Poor weight gain during the first weeks of life in preterm infants is associated with the risk of developing retinopathy of prematurity (ROP). Our study aimed to evaluate the effect of energy, macronutrient intake, and weight gain during the first 4 weeks of life on the risk of ROP.